2018
DOI: 10.1152/ajpheart.00187.2018
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional cardiac profile after prolonged duration of mechanical unloading: potential implications for myocardial recovery

Abstract: Clinical and experimental studies have suggested that the duration of left ventricular assist device (LVAD) support may affect remodeling of the failing heart. We aimed to (1) characterize the changes in calcium/calmodulin-dependent protein kinase type II (CaMKII)δ, growth signaling, structural proteins, fibrosis, apoptosis and gene expression before and after LVAD support and (2) assess whether the duration of support correlated with improvement or worsening of reverse remodeling. LV apex tissue and serum pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…A timely blockade of ACTRII after MI, at a time when pro-hypertrophic signaling has remitted, could be beneficial to prevent worsening wall thinning or aid in myocardial recovery programs. A second population that may benefit are HF patients supported with LV assisted devices (LVAD); these patients have increased MSTN levels and are at risk of myocardial atrophy with prolonged durations of LVAD support (1,11).…”
Section: Discussionmentioning
confidence: 99%
“…A timely blockade of ACTRII after MI, at a time when pro-hypertrophic signaling has remitted, could be beneficial to prevent worsening wall thinning or aid in myocardial recovery programs. A second population that may benefit are HF patients supported with LV assisted devices (LVAD); these patients have increased MSTN levels and are at risk of myocardial atrophy with prolonged durations of LVAD support (1,11).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies were conducted on circulating and cardiac myostatin in cardiomyopathies of various origins. Myostatin was found to be upregulated in myocardial cells of patients with dilated cardiomyopathy, but not with ischemic cardiomyopathy [ 170 ], and higher in abundance both in myocardium and in serum [ 171 ]. Fernandez-Sola et al, demonstrated cardiac myostatin upregulation in hearts with cardiomyopathy of hypertensive, alcoholic, valve and coronary origins [ 172 ].…”
Section: Factors Affecting Myostatin Concentrationmentioning
confidence: 99%
“…Clinical studies reveal that prognosis is similar with that in heart transplant (9)(10)(11). The most interesting observation was that, after being unloaded by the mechanical device for several months, some patients (not all) recover the contractility of the native myocytes.…”
mentioning
confidence: 71%